2014
DOI: 10.1016/j.juro.2013.07.065
|View full text |Cite
|
Sign up to set email alerts
|

Severe Testicular Atrophy does not Affect the Success of Microdissection Testicular Sperm Extraction

Abstract: Introduction and Objectives Men with azoospermia and severe testicular atrophy may be counseled to avoid sperm retrieval due to perceived limited success. We evaluated the outcomes of microdissection testicular sperm extraction (micro-TESE) in men with severe testicular atrophy (volume ≤ 2 mL). Methods We reviewed the records of 1127 men with nonobstructive azoospermia who underwent micro-TESE followed by intracytoplasmic sperm injection. The men were classified into three groups based on average testicular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
64
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 14 publications
6
64
1
2
Order By: Relevance
“…Similarly, regardless of sperm retrieval outcomes at microTESE, all iNOA men considered in our cohort showed reduced testicular volume. Despite testicular hypotrophy has been advocated to be associated with spermatogenic dysfunction 14 , current findings confirmed previous data showing that testis volume per se is not a reliable predictor of sperm retrieval outcomes at surgery 26 . To this must be added that primary hypogonadism in infertile men has been associated with low tT serum levels and high circulating FSH levels 27,28 .…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, regardless of sperm retrieval outcomes at microTESE, all iNOA men considered in our cohort showed reduced testicular volume. Despite testicular hypotrophy has been advocated to be associated with spermatogenic dysfunction 14 , current findings confirmed previous data showing that testis volume per se is not a reliable predictor of sperm retrieval outcomes at surgery 26 . To this must be added that primary hypogonadism in infertile men has been associated with low tT serum levels and high circulating FSH levels 27,28 .…”
Section: Discussionsupporting
confidence: 88%
“…In order to avoid confounding factors, we excluded patients with hypotestosteronemia, given that studies demonstrated that optimizing testosterone level may improve spermatogenesis [16] and increase SRR [17]. We also excluded patients with Y microdeletions, given that this clinical condition has been found to be an independent predictor factor for SSR [11] Our data are consistent to those of studies evaluating large cohorts of patients demonstrating that serum FSH level and testicular volume are not predictive of SSR when evaluated as the unique independent predictive factor [6,18,19]. The poor relationship between FSH level and spermatogenesis can be explained because FSH secretion and release is controlled by too many endocrine and paracrine factors that ultimately contribute to its serum levels, without ignoring the contribution of the polymorphisms in FSHB genotype and FSHR genotype that may lead to higher than expected FSH levels in some patients [20], so that a linear relationship between FSH serum level and spermatogenesis cannot be expected in all patients.…”
Section: Discussionsupporting
confidence: 54%
“…The poor relationship between FSH level and spermatogenesis can be explained because FSH secretion and release is controlled by too many endocrine and paracrine factors that ultimately contribute to its serum levels, without ignoring the contribution of the polymorphisms in FSHB genotype and FSHR genotype that may lead to higher than expected FSH levels in some patients [20], so that a linear relationship between FSH serum level and spermatogenesis cannot be expected in all patients. On the other hand, the poor predictive role of testicular volume can be explained by the presence of focal area of intact spermatogenesis that may be found even in patients with testicular atrophy [18,21]. Our data demonstrate that if we would rely on testicular volume to obtain indication for selecting the optimal candidates to surgical sperm retrieval, we would wrongly include and exclude from attempting surgery 32 and 50 % of patients, respectively…”
Section: Discussionmentioning
confidence: 80%
“…(6, 14, 19) In addition, a recent report looking at microTESE for a large series of NOA patients has shown that testis volume has no effect on successful sperm retrieval. (20)…”
Section: Discussionmentioning
confidence: 99%